Signs and symptoms, evaluation, and management of genitourinary tract consequences of premature ovarian insufficiency - Calik-Ksepka, Anna; Grymowicz, Monika; Rudnicka, Ewa; Skórska, Jolanta; Machura, Paulina; Pięta, Wojciech; Smolarczyk, Roman (Menopause Review/Przegląd Menopauzalny, 2018)
Premature ovarian insufficiency (POI) occurs in 1% of women under 40 years old. Hypoestrogenism associated with this condition may result in vaginal atrophy and urine incontinence, called genitourinary syndrome. The symptoms include: vaginal dryness, irritation, dyspareunia, and dysuria. There is relative lack of studies on the occurrence and treatment of genitourinary problems in women with POI. Prevalence rates vary from 17 to 54% depending on cause, duration of oestrogen depletion, and the treatment used. Patients with POI gain lower scores in tests measuring vaginal health or sexual function in comparison to healthy peers. Hormonal treatment in premature ovarian insufficiency is recommended until the natural age of menopause. The vaginal route of oestrogen administration is supposed to be the criterion standard in treating genitourinary symptoms. Androgen supplementation is not routinely recommended.